2022
DOI: 10.1021/acsami.2c01123
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Co-delivery of PD-L1 siRNA/Anemoside B4 for Enhanced Combinational Immunotherapeutic Effect

Abstract: Combination therapy has gained a lot of attention thanks to its superior activity against cancer. In the present study, we report a cRGDtargeted liposomal preparation for co-delivery of programmed cell death ligand 1 (PD-L1) small interfering RNA (siRNA) and anemoside B4 (AB4)AB4/siP-c-Land evaluate its anticancer efficiency in mouse models of LLC and 4T1 tumors. AB4/siP-c-L showed a particle size of (180.7 ± 7.3) nm and a ζ-potential of (32.8 ± 1.5) mV, with high drug encapsulation, pH-sensitive release pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 61 publications
0
13
0
2
Order By: Relevance
“…Intratumoral administration can be applied only locally and cannot allow nanoparticles to enter the distant tumor and tumor metastatic foci. Many other antitumor studies utilizing siPD-L1 also use intravenous injection. Therefore, this study used intravenous injection instead of intratumoral administration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Intratumoral administration can be applied only locally and cannot allow nanoparticles to enter the distant tumor and tumor metastatic foci. Many other antitumor studies utilizing siPD-L1 also use intravenous injection. Therefore, this study used intravenous injection instead of intratumoral administration.…”
Section: Resultsmentioning
confidence: 99%
“…PD-L1 plays a critical role in the transformation and proliferation of Tregs. PD-L1 can promote the transformation of Foxp3 + Tregs and its immunosuppressive function in vivo . It has been reported that the use of siRNA to downregulate the expression of PD-L1 in tumors is conducive to reducing the Tregs population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve enhanced lymphatic drug delivery system (LDDS), more advanced fundamental research is going on in the filed of lipid-based nanoparticles, dendrimers, liposomes, polymeric nanoparticles ( 2 ). In more conventional way to deliver medicines through LDDS approach, dermal injection is a promising approach ( 3 , 4 ). However, nanoscale materials are capable of crossing stratum corneum; which is basically a barrier which stops topically applied medicine from getting to where it needs to go.…”
Section: Introductionmentioning
confidence: 99%